Epigenetic dysregulation of KCa3.1 channels induces poor prognosis in lung cancer. Issue 6 (29th May 2015) - Bulk, Etmar; Ay, Anne‐Sophie; Hammadi, Mehdi; Ouadid‐Ahidouch, Halima; Schelhaas, Sonja; Hascher, Antje; Rohde, Christian; Thoennissen, Nils H.; Wiewrodt, Rainer; Schmidt, Eva; Marra, Alessandro; Hillejan, Ludger; et al.
<x xml:space="preserve">Abstract</x> Epigenomic changes are an important feature of malignant tumors. How tumor aggressiveness is affected by DNA methylation of specific loci is largely unexplored. In genome‐wide DNA methylation analyses, we identified the KCa3.1 channel gene (KCNN4) promoter to be hypomethylated in an aggressive non–small‐cell lung carcinoma (NSCLC) cell line and in patient samples. Accordingly, KCa3.1 expression was increased in more aggressive NSCLC cells. Both findings were strong predictors for poor prognosis in lung adenocarcinoma. Increased KCa3.1 expression was associated with aggressive features of NSCLC cells. Proliferation and migration of pro‐metastatic NSCLC cells depended on KCa3.1 activity. Mechanistically, elevated KCa3.1 expression hyperpolarized the membrane potential, thereby augmenting the driving force for Ca2+ influx. KCa3.1 blockade strongly reduced the growth of xenografted NSCLC cells in mice as measured by positron emission tomography–computed tomography. Thus, loss of DNA methylation of the KCNN4 promoter and increased KCa3.1 channel expression and function are mechanistically linked to poor survival of NSCLC patients.